DIPEPTIDYL PEPTIDASE-4 INHIBITORS INDUCED BULLOUS PEMPHIGOID: A REVIEW OF CURRENT CONCEPTS - Mirceska Arsovska, Elena (Acta medicae Medianae, 2025)
Bullous pemphigoid (BP) is a chronic, autoimmune, subepidermal blistering disease observed primarily in the elderly. Over the past two decades, there has been a substantial increase in BP incidence and prevalence in several countries worldwide. The reasons driving these increases include an increase in average life expectancy, better diagnostic methods, recognition of atypical variants of BP, and increased use of certain medications. Drug-associated BP (DABP) is a term used to describe cases of BP demonstrating clinical, histological, or immunopathological features identical or similar to those of the idiopathic form of BP, but associated with the systemic ingestion or topical application of particular drugs. Since the first report of DABP in 1970, more than 90 individual drugs have been reported associated with BP so far. The strongest evidence of an association with DABP is found in dipeptidyl peptidase-4 inhibitors, аlso known as gliptins, a relatively new class of oral antidiabetics. DABP should be considered a possible diagnosis in patients who have recently changed or added a new drug to their standard therapy. The temporal relationship between drug administration and the onset of BP is critical, and the culprit drug's withdrawal is the most crucial step toward clinical improvement.
Keywords: pemphigoid, bullous, dipeptidyl-peptidase 4 inhibitors, vildagliptin, diabetes mellitus